1988
DOI: 10.1172/jci113485
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucose transporters in the cellular insulin resistance of type II non-insulin-dependent diabetes mellitus.

Abstract: To examine the role of glucose transport proteins in cellular insulin resistance, we studied subcutaneous adipocytes isolated from lean control, obese control (body mass index [BMII 33.4±0.9), and untreated obese non-insulin-dependent diabetes mellitus (NIDDM) patients (BMI 35.2±2.1; fasting glucose 269±20 mg/dl). Glucose transporters were measured in plasma membrane (PM), low-density (LDM), and high-density (HDM) microsomal subfractions from basal and maximally insulin-stimulated cells using the cytochalasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
111
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 40 publications
9
111
0
2
Order By: Relevance
“…The reduced maximal insulin responsiveness and sensitivity of glucose transport in these cells may originate from a postinsulin binding and coupling defect between the insulin receptor and the translocation machinery and synthesis of GLUT mole cules, because we observed impaired redistribution of GLUT1 and GLUT4 from LDM to PM and a lowered total number of GLUT1 and GLUT4. Both reduced transloca tion and synthesis of GLUT4 are characteristic features for adipose tissue of obese and nonobese NIDDM pa tients (48,49). This suggests similar mechanisms of fat cell insulin resistance operating in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…The reduced maximal insulin responsiveness and sensitivity of glucose transport in these cells may originate from a postinsulin binding and coupling defect between the insulin receptor and the translocation machinery and synthesis of GLUT mole cules, because we observed impaired redistribution of GLUT1 and GLUT4 from LDM to PM and a lowered total number of GLUT1 and GLUT4. Both reduced transloca tion and synthesis of GLUT4 are characteristic features for adipose tissue of obese and nonobese NIDDM pa tients (48,49). This suggests similar mechanisms of fat cell insulin resistance operating in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…Adipose tissue glucose uptake and obesity M Stolic et al glucose uptake in isolated adipocytes in obese subjects 15,16 whereas others have found no changes. 14,17 In our study basal glucose transport was reduced in adipose tissue samples from overweight and obese compared to lean subjects, reaching statistical significance in obese subjects.…”
Section: International Journal Of Obesitymentioning
confidence: 99%
“…In view of these factors, our results are comparable with the results obtained using isolated human adipocytes. 15,21,22 For example, Garvey et al 15 reported a 1.7-fold increase in glucose uptake in lean subjects and a 1.3 fold increase in obese subjects and Marette et al 22 reported a 1.3 -fold increase in severely obese women. Only a few studies have examined differences in insulinmediated glucose uptake between intra-abdominal and subcutaneous adipose tissue.…”
Section: International Journal Of Obesitymentioning
confidence: 99%
“…
Impairment of the glucose transport in the insulinsensitive tissues contributes to the pathogenesis of Type II (non-insulin-dependent) diabetes mellitus [1,2]. Skeletal muscle represents the most important tissue for the maintenance of a balanced postprandial glucose homeostasis; about 80 % of insulin-stimulated glucose uptake is accounted for by muscle [3±5].
…”
mentioning
confidence: 99%